RRI Play Go: Revolutionizing Radio Broadcasting Through Media Convergence - Yusran Akbar; Muzakkir Muzakkir; Samwil Samwil (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
The development of information media in line with global advancements has facilitated access to communication and the exchange of information for individuals worldwide. Radio Republik Indonesia (RRI), as a public broadcasting medium, has adapted to the changing media landscape through the implementation of the RRI Play Go application. This study aims to analyze the development and implementation of RRI Play Go, focusing on RRI Meulaboh. A qualitative descriptive method was employed, involving direct observation and interviews with RRI Meulaboh employees. The findings reveal that RRI Play Go, as a digital radio platform, provides user-friendly features such as location-based broadcasts, access to educational content, live streaming, and interactive communication. Media convergence, facilitated by digitalization, has enabled RRI Meulaboh to maintain its relevance, expand its reach, and continue its mission of providing informative and educational content to the public.